Properties of nanosized cerium and copper oxide materials prepared from citrate solutions - Farbun, I. A.; Romanova, I. V.; Kirillov, S. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
Precursors for obtaining individual and mixed oxides of cerium (IV) and copper (II) have been synthesized from citrate solutions. Their composition has been determined by means of thermal analysis and IR spectroskopy. Oxides obtained by thermal treatment of precursors at 400 °С have been investigated by X-ray diffraction, scanning electron microscopy, and porosity measurements. These materials have been shown to be nanosized with the prevalence of mesopores.